Coprecipitation of Cefuroxime Axetil-PVP composite microparticles by batch supercritical antisolvent process - Uzun, Ipar Nimet; Sipahigil, Oya; Dincer, Salih (ELSEVIER SCIENCE BV, 2011)
Batch supercritical antisolvent precipitation (SAS) process was used to coprecipitate Cefuroxime Axetil amorphous (CFA, antibiotic) and Polyvinylpyrrolidone (PVP-K30) for preparing drug-polymer composite particles. Solutions of CFA and PVP-K30 in methanol with overall concentrations of 50-150 mg/ml and polymer/drug ratios of 1/1-4/1 were sprayed into the CO2 at 70-200 bar and 35-50 degrees C with drug + polymer solution injection rates of 0.85 and 2.5 ml/min. Spherical particles having mean diameters of 1.88-3.97 mu m, distribution ranges of 0.82-9.7 mu m (the narrowest distribution) and 0.91-46.64 mu m (the broadest distribution) were obtained. Mean particle size was not affected significantly with the change of process parameters. It was only affected by pressure change. On the other hand particle size distribution was affected by pressure, temperature, drug + polymer solution injection rate and concentration. It was observed that temperature and polymer/drug ratio affected the particle morphology most. The drug release rate of SAS-coprecipitated CFA-PVP (1/1) particles was almost 10 times slower than the drug alone. As the ratio of the polymer increased drug release rate also increased due to the wetting effect of PVP. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Cefuroxime Axetil amorphous; Polyvinylpyrrolidone; Coprecipitation; Composite microparticle; Supercritical antisolvent; SOLVENT-EXTRACTION SYSTEM; VAPOR-LIQUID-EQUILIBRIUM; COMPRESSED FLUID ANTISOLVENT; DIOXIDE PLUS METHANOL; CARBON-DIOXIDE; SOLID DISPERSIONS; BINARY-SYSTEMS; HIGH-PRESSURES; POLYMER PARTICLES; NANO-PARTICLES; Chemistry; Engineering